The first steps in the study of the Bulgarian language in Hungary - Yankova, Veneta (Slavica, 2024)
The article analyzes the handwritten notes from a book in the ELTE library (BOL/ Или-002), which preserves the testimonies of the activities of the first Hungarian Slavist, prof. Oszkár Asbóth (1852–1920). The only copy of the Collection of At. Iliev (1889) contains unique information about the beginning of academic Bulgarian studies in Hungary and restores lost traces of professional and personal contacts between Hungarian and Bulgarian scholars.